Successful management of free osteocutaneous fibula flap with anomalous vascularity of the skin paddle - Prabha S. Yadav; Quazi G. Ahmad; Vinay Kant Shankhdhar; G. I. Nambi (Indian Journal of Plastic Surgery)
The free osteocutaneous fibula flap is an established method of reconstruction of maxillary and mandibular defects. The vascularity of the skeletal and the cutaneous components is provided by the peroneal artery via the nutrient artery and the septo- and musculocutaneous perforators. In rare situations, these perforators may arise from other major leg arteries. In such circumstances, the procedure has to be either abandoned or modified so that neither the vascularity of the flap nor the donor limb is compromised. We present a case of an anomalous musculocutaneous perforator, which originated from the proximal part of the posterior tibial artery, passed through the soleus muscle and supplied the skin paddle. The flap was elevated as a single composite unit and was managed by two separate vascular anastomosis at the recipient site, one for the peroneal vessels and the other for the anomalous perforator.